MicroRNAs as Biomarkers for Animal Health and Welfare in Livestock - Miretti, Silvia; Lecchi, Cristina; Ceciliani, Fabrizio; Baratta, Mario (Frontiers in Veterinary Science, 2020)
MicroRNAs (miRNAs) are small and highly conserved, non-coding RNA molecules, which orchestrate a wide range of biological processes by post-transcriptionally regulating gene expression. An intriguing aspect in identifying these molecules as biomarkers derived from the active secretion from cells into the extracellular compartment and their high stability in body fluids. There is a growing interest in the importance of miRNA as well-being and health biomarkers for assessing welfare during metabolic, environmental and management stress in livestock and in particular, ruminants, pig and poultry. This review provides an overview of the states of art about the potential use of tissue and/or circulating miRNAs as biomarkers for the identification of welfare or health status in these livestock species.